Machine learning algorithm as a sustainable tool for dissolved oxygen prediction: a case study of Feitsui Reservoir, Taiwan - Ziyad Sami B.F.; Latif S.D.; Ahmed A.N.; Chow M.F.; Murti M.A.; Suhendi A.; Ziyad Sami B.H.; Wong J.K.; Birima A.H.; El-Shafie A. (Nature Research, 2023)
oxygen; algorithm; environmental monitoring; machine learning; procedures; reproducibility; Taiwan; water quality; Algorithms; Environmental Monitoring; Machine Learning; Oxygen; Reproducibility of Results; Taiwan; Water Quality